(untitled) (Malaysian Management Journal, 2021)
This study examined the effect of nominal exchange rate depreciation on the trade balance in 11 Asian-African countries between 1980 and 2019, and within the context of an exogenously determined single structural break. The countries had persistently experienced both nominal exchange rate depreciation and upward trends in trade in goods. Using the Chow test to frame the discussion, these countries were found to be facing structural changes associated with external factors such as the commodity price crisis in South Asia and the global financial crisis. The time-series autoregressive distributed lag (ARDL) approach with bounds test for cointegration and error-correction mechanism (ECM) was also applied for the analysis. The results of the study showed a long-term cointegration between the trade in goods and other variables included. Specifically, the nominal exchange rate depreciation positively affected the trade in goods in both the long-run and short-run in most of the Asian-African countries studied. There was a positive relationship between trade and foreign direct investment in the short-run, but this relationship mostly became insignificant in the long-run. Gross domestic product had a significant impact on trade performance in goods in both the long-run and short-run in all countries studied.